Setting standards for a diagnostic test of aviation English for student pilots - Treadaway, Maria; Read, John (Language testing, 2024)
Standard-setting is an essential component of test development, supporting the meaningfulness and appropriate interpretation of test scores. However, in the high-stakes testing environment of aviation, standard-setting studies are underexplored. To address this gap, we document two stages in the standard-setting procedures for the Overseas Flight Training Preparation Test (OFTPT), a diagnostic English test for ab initio pilots, aligned to the International Civil Aviation Organization (ICAO)’s Language Proficiency Rating Scale (LPRS). Performance-level descriptors (PLDs) were empirically generated in Stage 1 in collaboration with six subject matter experts (SMEs). These PLDs made explicit the correspondence between linguistic performance levels within the target language use domain and the ICAO scale. Findings suggest that the ICAO scale is not fine-grained enough to distinguish levels of linguistic readiness among ab initio pilots, nor does it adequately reflect the knowledge, skills, and abilities valued by SMEs within this domain. In Stage 2, 12 SMEs were recruited to set standards and were divided into two groups to investigate the replicability of Ebel method standard-setting procedures. Cut scores were determined for the OFTPT reading and listening tests, which were inferentially linked to the LPRS. There were no significant differences in the cut scores arrived at by both groups and reliability was excellent, suggesting that test users can have confidence in the standards set.